A Bibliometric Review of Tempeh Research: Trends, Collaborations, and Emerging Themes (1928–2025) - Hasniah, Nurul; Aziz, Fariz Nurmita; Kamil, Rafli Zulfa; Akter, Tanjina (Diponegoro University, 2025)
Tempeh, a traditional Indonesian fermented soybean product, has garnered increasing global attention due to its rich nutritional profile, health benefits, and suitability as a sustainable alternative protein source. This study presents a bibliometric analysis of tempeh-related scientific publications retrieved from the Scopus database, aiming to map the evolution of research, identify leading contributors, and uncover prevailing and emerging research trends. A total of 897 documents published between 1928 and 2025 were analyzed using VOSviewer to generate visualizations of keyword co-occurrences and bibliographic data. The results show a notable rise in tempeh research after 2010, with significant contributions from Indonesian institutions and increasing global interest. Thematic clusters identified include microbiological fermentation, nutritional and technological applications, animal-based functional food studies, and clinical health research. This study highlights tempeh’s expanding role in functional food science and emphasizes opportunities for interdisciplinary collaboration and further research, particularly in underexplored health and sustainability dimensions.